2019
DOI: 10.1155/2019/5276824
|View full text |Cite
|
Sign up to set email alerts
|

Plant Diversity and Ethnoveterinary Practices of Ethiopia: A Systematic Review

Abstract: The systematic review was conducted on Ethnoveterinary Medicinal (EVM) plants from the two (integrated and pastoral) majorly known livestock production systems (LPS) of Ethiopia. A total of 48 documents pertinent to EVM significance were assessed from different sources using Google search engine and local university websites. Search outputs were screened using the developed inclusion criteria, and only 26 documents were selected. Descriptive analysis measures, Document Consensus Factor (DCF), and rank of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Majority of the honey types which were used for treating ailments in this study have been majorly administered through oral route. This result is in line with many plant and animal based ethno pharmacological medicines [28,31,33,34,58]; ethno zoological products used to treat ailments [58,59]. This might be due to the cautious oral administration of honey would render the digestive system aseptic and disease-causing germs would fail to thrive.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Majority of the honey types which were used for treating ailments in this study have been majorly administered through oral route. This result is in line with many plant and animal based ethno pharmacological medicines [28,31,33,34,58]; ethno zoological products used to treat ailments [58,59]. This might be due to the cautious oral administration of honey would render the digestive system aseptic and disease-causing germs would fail to thrive.…”
Section: Discussionsupporting
confidence: 72%
“…For ethno-pharmacological experimental or clinical investigations, a relevant starting point is to understand who uses traditional medicine [28].To gain new honey ethno pharmacological knowledge, innate and long years of acquired beekeepers and healer's knowledge and skill towards the source and it accuracy of healing is very crucial [28]. Furthermore, quantitatively analysis of ethno-pharmacological use of natural products can provide huge significance in the process of subjective interpretation, experimental trial and drug development [29].Several ethno pharmacological studies and reviews [28,[31][32][33][34], has been done in Ethiopia. However, the majorities were purely ethno botanical studies, and studies related to honey medicine based of their plant origion has been very short and overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 15 plant species used for treating livestock ailments in the area, 14.3% of species were shrubs. A study conducted by Mesfin et al (2009) and Tilahun et al (2019) indicated that the shrubs were identified as a major plant habit harvested for livestock disease treatment with 40% and mean of 32.05, respectively. However, the findings of Teklehaymanot and Giday (2007) showed that herbs (52%) were the most frequently used plant habit.…”
Section: Growth Form and Part Of Medicinal Plants Used To Treat Livesmentioning
confidence: 99%
“…The popularity of phytomedicines intended for use in bovines and sheep-goats is proportional to the weight that these species have in the production of meat, milk, cheese, and leather. The husbandry of these three polygastric animals is essential both for household survival and for increasing economic capital and social prestige in pastoralist and peasant societies (McGaw et al, 2020;Tilahun et al, 2019). Despite the overwhelming dominance of the productive species, it is important to point out the presence of pets in the medical and food sectors, with dominance in phytogenic additives.…”
Section: Resultsmentioning
confidence: 99%